The effect of carbon nanoparticles on biological properties of polyester nanocomposites. (May 2017) - Staniszewski, Zygmunt; Piegat, Agnieszka; Okroj, Wieslawa; Walkowiak-Przybylo, Magdalena; Jakubowski, Witold; Walkowiak, Bogdan; Budner, Boguslaw; Mroz, Waldemar; Sobolewski, Peter; El Fray, Miroslawa
The aim of present study was to determine the hemocompatibility, cellular response of endothelial cells and bacterial adhesion to a new polyester nanocomposite. The carbon nanoparticle nanocomposite was prepared via in situ polymerization of monomers to obtain material of hardness 55 Sh D similar to polyurethanes used in medical applications, for example, in heart-assisting devices. The carbon nanoparticle-containing polyester exhibits markedly reduced bacterial colonization, as compared to commercially available polyurethanes. Further the nanocomposite possesses markedly improved hemocompatibility, as determined by flow cytometry, and robust endothelialization. Possible explanations for these beneficial properties include surface nanoroughness of carbon nanoparticle-containing nanocomposites and presence of fatty acid sequences within polymer structure.